A dimensão educativa do serviço social: uma análise do processo interventivo da profissão no âmbito da política de assistência social do município do Natal/RN - Cavalcante, Suzanny Bezerra (2010)
Can be declared that throughout the historical trajectory of the Brazilian Social Work, the men in the Social Work profession, women in the Social Work profession in his/her professional activity, present an educational dimension that runs through various social and occupational spaces, particularly in the area of Social Assistance Policy. Based on this premise, this present Dissertation, problematize the educational dimension present on the interventional process, in Social Work on the ambit of the Social Assistance Policy in Natal / RN city Brazil in the contemporary scene. Having thus, specific objectives that orientate the research of the interventional process of Social Work in the social assistance policy, analyzing of the apprehension of Social Work professionals on the educational dimension, in their daily work professional and the verification of the relationship between the educational dimension, to the professional action of both men in the Social Work profession and women in the Social Work profession and the concretization of social rights on the ambit of the social assistance policy. In this sense, the theoretical and methodological procedures used for this research, are substantiated on a critical-dialectical perspective and a qualitative and quantitative approach, from of the application of field research, of the non-participant observation, of the semi-structure, of the review of literature bibliographic and documental. Thus, considering that both women in the social work profession and men in the social work profession are an organic intellectuals who in their daily professional work promotes an intellectual and moral reform of their users, the results of this research, synthesize and show that the educational dimension in both professional work and social assistance, which have partner-historics, whose imbrication allows, contradictorily, by a side, a reaffirmation of the dominant culture, and by other side, a direction linked to the construction of an emancipatory culture in the pursuit of the materializing of social rights and a new sociability